The Influence of Empowerment and Transformational Leadership on Member Welfare with Farmers Group Performance as a Mediation Variable (Case Study in Ampar Adhum Farmers Group) - Muhammad Faqih As Shiddieq; Sutisna Sutisna; Sulaeman Rahman Nidar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
DKI Jakarta faces the issue of low productivity in the agricultural sector, contributing only 0.49% to the regional economy and relying on food supplies from other regions up to 98% (BPS, 2021). The Ampar Adhum Farmer Group conducts integrated hydroponic farming activities in Cipinang Besar Utara, Jatinegara District, Jakarta, as an alternative food producer with a productivity rate of 70 kg/day. Since 2018, this farmer group has implemented an empowerment program aimed at improving the welfare of its members. This study aims to analyze the influence of empowerment and transformational leadership on the welfare of the Ampar Adhum Farmer Group members with performance as a mediating variable. The data analysis method used is Structural Equation Modelling (SEM) based on a Likert scale questionnaire distributed to all group members. Out of a total of 110 members, 54 were sampled for the study. The results indicate that empowerment does not significantly affect members' welfare, while transformational leadership has a significant impact. Furthermore, performance does not significantly mediate the effect of empowerment and transformational leadership on members' welfare.